LANGUAGE AND SPEECH LEVELS. GRAMMATICAL FORM AND MEANING. (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
This article explores the relationship between language and speech levels, focusing on how grammatical forms convey meaning. It examines the role of grammar in structuring language, enabling effective communication and comprehension across different contexts. By analyzing the connection between grammatical structure and semantic meaning, the study highlights how variations in language and speech levels can affect the interpretation and clarity of messages. This understanding is essential for both language learners and linguists, as it deepens insight into the complexities of language use and development.